Methodisches und Sachliches zum Circumcellionentum - Diesner, Hans-Joachim (Wissenschaftliche Zeitschrift der Martin-Luther-Universität Halle-Wittenberg‎. Gesellschafts- und sprachwissenschaftliche Reihe, 1959)
Keywords: Donatisme

Were Ancient Heresies National or Social Movements in Disguise? - Jones, A. H. M. (The Journal of Theological Studies, 1959)
Keywords: Donatisme

Le imprese contro Tripoli e l'isola di Gerba dal 1284 al 1560 - Longhena, Mario (Atti dell'Accademia di agricoltura, scienze e lettere di Verona, 1959)
Keywords: Invasions chrétiennes – Djerba

À propos d’une liste des tribus berbères d’Ibn Ḥawqal - Lewicki, Tadeusz (Folia Orientalia, 1959)

Tunisiens et Maghrébins au Caire au 18ième siècle - Raymond, André (Cahiers de Tunisie, 1959)
Keywords: Emigration – Djerba – Egypte

Les Ibāḍites dans l’Arabie du Sud au moyen-âge - Lewicki, Tadeusz (Folia Orientalia, 1959)
Based mainly on Sunnī sources. Furthermore, i.a., on: - Shammākhī: Siyar; - Darjīnī: K. Ṭabaqāt al-Mashāyikh; al-Siyar al-ʿUmāniyya; - ʿAbdl. b. Ḥumayyid al-Sālimī: al-Lumʿa al-Murḍiya; - Masqueray 1878a, Chronique d’Abou Zakaria; - Abū Isḥāq Ibr. b. Qays al-Ḥaḍramī: Dīwān al-Sayf al-Naqqād.
Keywords: Ibadisme – Yemen

Un document ibāḍite inédit sur l’émigration des Nafūsa du Jabal dans le Sāḥil tunisien au VIIIe/IXe siècle - Lewicki, Tadeusz (Folia Orientalia, 1959)
Keywords: Emigration – Djebel Nefousa – Tunisie

Les travaux de T. Lewicki concernant le Maghrib et en particulier les Ibāḍites - Canard, Marius (Revue Africaine, 1959)
Keywords: Recension

Découverte à Tihert-Tagdempt d’un “Dénéral” d’époque fatimide - Cadenat, Paul (Revue Africaine, 1959)
Keywords: Numismatique – Tahert

al-Makhṭūṭāt al-ʿArabiyya fī Būlūnyā - Kubiak, Wladyslaw (مجلة معهد المخطوطات العربية, 1959)
The following Ibāḍī MSS are mentioned: - nr. 4: K. Ansāb al-ʿArab of Salma b. Muslim al-ʿAwtabī (al-ʿAwnī) al-Ṣuḥārī; (Dembski, 85-86 nr. 4) - nr. 8: a small part of an Ibāḍī MS, a modern copy, n.d. and no author, on Sīrat al-A’imma al-Ibāḍiyya wa-Tārīkhihim, containing a part of a book of Ibn al-Ṣaghīr; (Dembski, 72 nr. 31) - nr. 18: Darjīnī: K. Ṭabaqāt al-Mashāyikh; (Dembski, 77 nr. 42) - nr. 19: Warjlānī, Abū Zak. Yaḥyà b. Abī Bakr: K. al-Sīra wa-Akhbār al-A’imma, part 1; (Dembski, 77 nr. 43, 78 nr. 44, 79 nr. 46, 82 nr. 52; 84 nr. 55, 3) - nr. 20: second part of the same; (id.) - nr. 21: a complete copy of the same; (id.) - nr. 22a: Anonymous: K. Sīrat al-Madhhab wa’l-A’imma wa-ʿUlamā’ihim wa’l-Imāma, a large part of it; (Dembski, 78-79 nr. 45) - nr. 22b: Anonymous: Azhār al-Riyāḍ fī Akhbār al-Riyāḍ, another title for 22a; - nr. 23a: Anonymous: Akhbār Waqā’iʿ Jarba, the Christian attack on Jerba in 916/1510-11; (Dembski, 79-80 nr. 47) - nr. 23b: Anonymous: a Qaṣīda on the same subject as 23a; (Dembski 80 nr. 47, 2) - nr. 23c: Anonymous: Qaṣīda Ibāḍiyya ʿan il-Maghrib; (Dembski 80 nr. 47, 3) - nr. 23d: Anonymous: Tārīkh Warghla wa-Sadrāta; (Dembski 80 nr. 47, 4) - nr. 23e: Anonymous: Tārīkh Mzāb; (Dembski 80 nr. 47, 5) - nr. 24: Anonymous: Dhikr baʿḍ Biqāʿ Fāḍila wa-huwa Waṣf Biqāʿ Ibāḍiyya fī Mzāb; (Dembski, 80 nr. 48) - nr. 25: Mudabdaḥī, Basmaʿīn (copyist?): K. ʿAjab al-Iʿjāb al-Muntakhab min Aḥwāl Banī Mzāb; (Dembski, 81 nr. 49) - nr. 26: Tanāwutī, Abū ʿAmmār ʿAbd al-Kāfī: K. Sharḥ al-Jahālāt; (Dembski, 81-82 nr. 51) - nr. 27: Anonymous: Bayān al-Tawārīkh, part of the history of Mzāb; - nr. 28: Anonymous: hādhihi Nasab Sadrātan wa-ʿImārat al-ʿAṭf wa-Nasab Awlād ʿAbdl., short articles on the history of Mzāb and Sedraten; (Dembski, 87-88 nr. 2) - nr. 30: Shammākhī: K. al-Siyar; (Dembski, 88-89 nr. 4) - nr. 31: Anonymous: a smal part of an Ibāḍī book on Siyar al-Mashāyikh; (Dembski, 83 nr. 55, 2) - nr. 32: Anonymous: part of an Ibāḍī book on Fiqh.
Keywords: Manuscrits – Cracovie

'Omān - A. d. C. (Oriente Moderno, 1959)
Keywords: Relations – Oman – Royaume-Uni

'Omān - V., V. (Oriente Moderno, 1959)

Lewicki, Tadeusz: Études Ibadites Nord-Africaines - Strothmann, Rudolph (Orientalistische Literaturzeitung, 1959)
Keywords: Recension

Die Palmengärten des Mzab - Suter, Karl (Mitteilungen der Österreichischen Geographischen Gesellschaft, 1959)
Keywords: Géographie – Mzab

L’habitation djerbienne - Combès, Jean-Louis (Cahier des Arts et Techniques d'Afrique du Nord, 1959)
Keywords: Architecture – Djerba

Mzab actualités - Moriaz, Jean (Bulletin de Liaison Saharienne, 1959)
Keywords: Moeurs et coutumes – Mzab

Zuara Berber personals - Hamp, Eric P. (Bulletin of the School of Oriental and African Studies, 1959)
Keywords: Linguistique – Zouara

Tiaret - Cadenat, Paul (Libyca, 1959)
Keywords: Archéologie – Mzab

Note sur la teinture dans le territoire de Ghardaïa - Bonète, Yves (Cahier des Arts et Techniques d'Afrique du Nord, 1959)
Keywords: Artisanat – Mzab

Contribution à l'étude de l'habitat au M'zab - Bonète, Yves; Bonète, Yvette (Cahier des Arts et Techniques d'Afrique du Nord, 1959)
Keywords: Urbanisme – Mzab

Teinture végétale dans le sud tunisien - Coustillac (Cahiers des arts et techniques d’Afrique du Nord, 1959)
Keywords: Artisanat – Djerba